A profissão docente presa na armadilha da crise: a avaliação dos professores contemporizada no jugo da crise ou uma alternativa para a sua mitigação - Henrique Manuel Pereira Ramalho (Escola Superior de Educação de Paula Frassinetti, 2012)
At a time when we look at the evaluation in one way made sacred, we provide a more incisive attention on the assessment of teacher performance, while consolidation factor to important educational changes for the resolution of the crisis which we live. With this paper, we undertook an exercise in a new interrogation the assessment of the teachers, listing it in a context of a crisis and inducing it as singular educational policy, now enrolled in a prospective condescending of the crisis, now a mitigation perspective of the current state of social and economic disturbance. For this, we proceed to a short analysis exercise of the paradigmatic changes may influence the understanding and the contribution of teacher performance assessment in scope to the exit of the social crisis. We synthesized our approach about the effect of accommodating the established narratives of the teacher performance assessment and, alternatively, the dissent of the instituting perspectives with mitigating effect of the crisis.